Sahridayata as a Pathway to Peace: Examining Its Implications in Conflict Resolution within the Context of the Ethnic Conflict in Manipur - Das, Rupam Kr (Bodhi: An Interdisciplinary Journal, 2024)
This paper seeks to unravel the implications of Sahridayata-based interventions, including indigenous peace-making traditions, citizen-centric dialogues, and truth-telling initiatives that have been appliedin Manipur for conflict resolution and peacebuilding. Also, this scholarly endeavour aims to contribute to a deeper understanding of empathy-driven approaches in conflict resolution and pave the way for sustainable peace initiatives in Manipur and beyond. Manipur, a northeastern state of India, recently witnessed unprecedented violence in the first week of May 2023 between the Meitei and the Kuki ethnic communities. When most of the news media reports pointed out the 3rd May incident in the Kuki-majority district of Churachandpur to be the root cause of the violence, an alternative forum advocated that it was the Meitei groups’ act of blocking the roads in the Imphal East District. Sahridayata acts as a powerful facilitator of understanding, empathy, and reconciliation that are necessary for successful conflict resolution. In the context of conflict resolution, it makes individuals and parties related to one another by making them put themselves into other individuals or parties’ shoes and understand their emotions. Sahridayata encourages individuals and parties involved in a conflict to create a comfortable and safe space for dialogue and communication. Sahridayata is also related to forgiveness and the ability to move on and heal after the end of the conflict. By fostering a culture of forgiveness and promoting reconciliation processes, Sahridayata contributes to building bridges and repairing fractured relationships.